1999
DOI: 10.1017/s0950268899002137
|View full text |Cite
|
Sign up to set email alerts
|

A high proportion of Vibrio cholerae strains isolated from children with diarrhoea in Bangkok, Thailand are multiple antibiotic resistant and belong to heterogenous non-O1, non-O139 O-serotypes

Abstract: Results of a surveillance on cholera conducted with patients seen at the Children Hospital in Bangkok, Thailand from August 1993 to July 1995 are presented. Annually, isolation rates for Vibrio cholerae varied between 1.7 and 4.4% of patients with diarrhoea. V. cholerae O1 serotype Ogawa accounted for between 31 and 47% of patients cultured positive for V. cholerae, whereas the O139 serotype dominated in early 1994 after which it disappeared. Non-O1, non-0139 strains were isolated at similar rates as serotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 49 publications
5
57
1
9
Order By: Relevance
“…Although the re-arrangement and copy number of the virulence cassette may play an important role in determining the pathogenicity level of the isolates [34], the presence of a virulence cassette could be variable, as it is subjected to amplification and deletion under the control of the recA gene [34]. Moreover, the data obtained in the present study were also in accordance with other reports [35][36][37], i.e., V. cholerae non-O1, non-O139 strains rarely harbour cholera toxin genes or other virulence genes contained in the virulence cassette found in O1 and O139.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although the re-arrangement and copy number of the virulence cassette may play an important role in determining the pathogenicity level of the isolates [34], the presence of a virulence cassette could be variable, as it is subjected to amplification and deletion under the control of the recA gene [34]. Moreover, the data obtained in the present study were also in accordance with other reports [35][36][37], i.e., V. cholerae non-O1, non-O139 strains rarely harbour cholera toxin genes or other virulence genes contained in the virulence cassette found in O1 and O139.…”
Section: Discussionsupporting
confidence: 91%
“…Ribotyping with the Bgll restriction endonuclease produced four distinct patterns amongst the V. cholerae isolates in this study, three of which were in serotype O1 isolates, and the fourth in non-O1, non-O139 isolates. Ribotype pattern 1 was a representative of non-O1, non-O139 V. cholerae isolates in Iran, which was similar to that reported by Dalsgaard et al [36] in Thailand. Pattern 2 was recognised as V. cholerae O1 ribotype B15 in our database.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Both clinical and environmental strains of V. cholerae (O1 and non-O1) which are multiply resistant to antimicrobial agents have been reported with increasing frequency (5,7,(11)(12)(13). Even though some reports demonstrated that the presence of antibiotic resistance genes in plasmids or integrons in V. cholerae were the cause of resistance to antimicrobial agents, the mechanisms of resistance in other cases are unknown and remain to be determined (5,7,28). Therefore, we are investigating the possible involvement of multidrug efflux pumps as the causative agent of multidrug resistance in V. cholerae.…”
mentioning
confidence: 99%